Couples Relationship Education and Couples Therapy: Healthy Marriage or Strange Bedfellows?. Issue 4 (7th November 2015) - Markman, Howard J.; Ritchie, Lane L.
Abstract : This paper focuses on issues sparked by the Couples Relationship Education (CRE) field moving toward a more clinical model to meet the needs of an increasing number of distressed couples coming to CRE programs. We review the concerns raised and recommendations made by Bradford, Hawkins, and Acker (2015), most of which push CRE toward a more clinical model. We address these recommendations and make suggestions for best practices that preserve the prevention/education model underlying research‐based CRE. The three main issues are couple screening, leader training, and service delivery models. Our suggested best practices include: conducting minimal screening including the assessment of dangerous levels of couple violence, training leaders with key skills to handle issues raised by distressed couples as well as other couples who may place additional burdens on leaders, providing referrals and choices of programs available to participants at intake and throughout the CRE program, and adding (rather than integrating) clinical services to CRE services for couples who desire additional intervention. Finally, throughout the paper, we review other key issues in the CRE field and make recommendations made for future research and practice.